The perception of english language teaching-learning as FL/L3 by ICEPSA-Altamira deaf in non-bilingual schools - LANGER, Rosiane dos Santos (2023)
This paper aims to investigate how the teaching-learning process of English as a foreign language occurred in regular public schools in Altamira from the perceptions of deaf students associated with the Instituto Cultural Educacional e Profissionalizante dos Surdos de Altamira (ICEPSA), addressing the main problems experienced in that school context. For this qualitative research four pre-selected deaf students were chosen. Concerning the theoretical references, the studies of Spasiani (2018), Roque (2018) and Silva (2019), among other authors who discuss the relationship of deaf learners in the educational environment. The data collected were acquired through the application of questionnaires and semi-structured interviews and the results were described in three categories specified in the scope of this work, which point to the lack of interpreters of Libras in the classroom, as well as the lack of teaching materials suitable for deaf students. However, there is a recognition of the importance of learning English as L3 in the current individual and global scenario.